Stability of highway embankments constructed on sloping ground against translational failure - Pantelidis, Lysandros (My University, 2008)
A translational failure of a highway embankment constructed on sloping ground may occur either in the mode of overall instability or in the mode of local instability. The stability analysis of the first mode is based on the assumption that the whole cross-section of the embankment will slide along the inclined base surface, whilst the second mode is based on the assumption of Rankine's active state of stress. In this paper the determination of the prevalent mode of failure – overall or local – is provided via a chart derived from force polygon analysis, with the dimensionless parameter, c′/γH, and the effective friction angle, φ′, as its axes. Furthermore, the determination of the most probable failure plane in the cross-section of the embankment is attempted and additionally the role of the cohesion in the stability is discussed. Finally, an estimation of the amplitude of failure at the road surface in the case of local instability is given. A confirmation of the aforementioned was achieved through case studies of highway embankments that have failed as a consequence of water infiltration and the development of high pore water pressures. A comparison between the local and the respective overall instability safety factor is given.
Keywords: Active pressure; Highway embankments; Safety factor; Sloping ground; Stability; Translational failure